Radiomonitoring in the Dairy Farm “Sotarboev Muzaffar” Located in the Citizens’ Assembly Territory of Amudarya District, Republic of Karakalpakstan - B.N. Khakimov; B.Sh. Mirzayev; J.R. Ayupova (American Journal of Botany and Bioengineering, 2026)
This article presents data on radiometric research conducted at the dairy farm “Sotarboev Muzaffar” located in the citizens’ assembly territory of Amudarya district, Republic of Karakalpakstan. Soil, alfalfa, water reservoirs, and hay samples collected from the farm area were analyzed under laboratory conditions. Detailed results of radiometric measurements and laboratory investigations are provided.